Design and Development of a Hand Exoskeleton Robot for Active and Passive Rehabilitation. (8th April 2016) - Sandoval-Gonzalez, Oscar; Jacinto-Villegas, Juan; Herrera-Aguilar, Ignacio; Portillo-Rodiguez, Otniel; Tripicchio, Paolo; Hernandez-Ramos, Miguel; Flores-Cuautle, Agustín; Avizzano, Carlo
The present work, which describes the mechatronic design and development of a novel rehabilitation robotic exoskeleton hand, aims to present a solution for neuromusculoskeletal rehabilitation. It presents a full range of motion for all hand phalanges and was specifically designed to carry out position and force-position control for passive and active rehabilitation routines. System integration and preliminary clinical tests are also presented.